Health effects among workers in sewage treatment plants. Issue 5 (1st May 1999) - Rylander, R
Abstract : OBJECTIVES: To further assess the presence of fatigue, symptoms of diarrhoea, and inflammation of airways among people working in sewage plants and the relation to airborne bacterial endotoxin at the workplace. METHODS: 34 Employees in sewage treatment plants and 35 controls were selected. They underwent a questionnaire investigation, and spirometry and airway responsiveness were measured. Measurements were made of airborne endotoxin at different workplaces. RESULTS: The amount of airborne endotoxin varied between 3.8 and 32, 170 ng/m3. Workers reported significantly higher nose irritation, tiredness, and diarrhoea. Airway responsiveness was increased among sewage workers, but no differences between the groups were found for spirometry. CONCLUSIONS: The results confirm previous studies on the presence of airways and intestinal inflammation among workers in sewage treatment plants. The most likely causative agent is endotoxin, and at 14 of 23 workplaces, concentrations exceeded recommended guidelines.